Inflammatory Mediators in Abdominal Aortic Aneurysms - Cassimjee, I; Lee, R; Patel, J (Intech Open, 2017)
Aortic wall dilatation in abdominal aortic aneurysms is characterized by extracellular matrix degradation together with a loss of smooth muscle cells from the aortic media. This occurs in conjunction with a marked inflammatory cell infiltration. The inflammatory cell is characteristic of the second phase of aneurysmal development–progression. It is widely accepted that usually there are three phases involved in the development of abdominal aortic aneurysms: initiation, progression and rupture. In this chapter, we present an overview of the inflammatory mediators in abdominal aortic aneurysms and intraluminal thrombus, highlighting evidence from experimental models and human disease.